India's Early Childhood Care and Education (International Journal of Innovative Research in Engineering & Management, 2021)
The first six to eight years of a child's life  are the most crucial in their development!! Because of the  rapid pace of growth throughout these years, the early  childhood era is typically considered as the most critical  for life-long development. "Experience-based brain  development in the early years develops neurological and  molecular pathways that impact health, learning, and  behavior throughout life," according to recent  neuroscience studies. These early years of life are critical  for the development of numerous cognitive, social, and  psychomotor abilities that contribute significantly to later  life success. If a stimulating and enriching physical and  psychological environment is not provided during these  critical ages, the chances of the child's brain developing to  its full potential are considerably reduced, and sometimes  permanently. According to the conclusions of this  research, a considerable number of poor children,  particularly in developing nations, are "at risk" in terms of  their future chances. “In many nations, disadvantaged  children have a significant cognitive and social  disadvantage by the time they reach school age.
Keywords: Childhood Care; Childhood Development; Developing Countries; Early Education; State Duty